Assessment of a system for the prediction of water permeability coefficient in pervious concretes - Ribeiro,A. (2018)
Abstract Proposing a system which makes it possible to determine the water permeability coefficient in pervious concretes in a practical way, without the need of devices which require complex instrumentation, is one of the aims of this work. An experimental matrix was proposed for the evaluation of the measurement system of the coefficient of permeability into pervious concrete considering three different pervious concretes obtained from different aggregate granulometric sizes, under the condition of dry sample or water saturated. The pervious concretes were characterized by their void contents, mechanical properties and later compared with the properties of a reference, control concrete made up of coarse and fine aggregates. The different properties exhibited in this study were assessed aiming at validating the experimental matrix developed for pervious concretes to provide a basis for comparison with information available in the literature. As a noticeable result, it was evidenced that the permeability coefficient of 0.21 cm.s-1 obtained for concrete with aggregate dimensions of 2.4 to 9.5 mm. It is possible to measure the coefficient of permeability of pervious concrete with the system developed in this study; the obtained results agree with the description of ACI522-06 for pervious concretes.